PELATIHAN PENULISAN PENELITIAN TINDAKAN KELAS DALAM PROSES PEMBELAJARAN PADA GURU-GURU SEKOLAH DASAR NEGERI 106162 MEDAN ESTATE - Johannes Keliat S.Pd. M.Pd; Bunga Fisikanta Bukit S.Si, M.Si; Susanti Br Sinaga (JURNAL CURERE, 2022)
Community service is carried out in order to fulfill the Tridharma of Higher Education. This activity is in the form of "Classroom Action Research Writing Training in the Learning Process for State Elementary School Teachers 106162 Medan Estate". This Classroom Action Writing Training aims to improve teacher teaching patterns, improve student behavior, improve learning practices, change the teacher's framework in teaching so that there is an increase in teacher professionalism. The Class Action Writing Training activity was carried out by the Community Service Team, namely an Elementary School Teacher Education Lecturer (PGSD) Faculty of Teacher Training and Education, Quality Berastagi University as a resource person and one of the students of the Elementary School Teacher Education Study Program as a member. Classroom Action Writing Training was held on Monday, November 22, 2021 using the lecture method related to Classroom Action Research Writing. The results of the Class Action Writing Training are in the form of Systematics in making Proposals and Systematics of Classroom Action Research Results Reports. Participants of the Class Action Writing Training were very enthusiastic about participating in the training provided by the Community Service Team to gain Knowledge Insights in Class Action Writing.